Development of an Innovative Spray Device for Slimline Dishwashers - Larsson, Filip; Örtenfelt, Robin (My University, 2025)
This thesis investigates how water coverage can be improved in new slimline dishwasher models by developing an innovative spray device concept. Slimline dishwashers are valued for their compact size but often face limitations in cleaning performance due to restricted water distribution. The project followed a structured design methodology, including generating product specifications, concept creation, concept selection, prototyping, and testing. Several promising design concepts were explored, with one in particular demonstrating superior spray coverage while remaining viable across multiple evaluation criteria. The findings suggest that more effective dish-cleaning solutions are possible through targeted design improvements that address the unique challenges of compact appliances. However, further research is needed to refine the concept, as well as assessment of its long-term performance and potential for integration into commercial dishwasher models
Keywords: Product Development; Innovative Solution; Dishwasher; Water-Area-coverage; Bottom Spray Arm; Reciprocating Movement